Observation of limb movements reduces phantom limb pain in bilateral amputees. (September 2014) - Tung, Monica L.; Murphy, Ian C.; Griffin, Sarah C.; Alphonso, Aimee L.; Hussey‐Anderson, Lindsey; Hughes, Katie E.; Weeks, Sharon R.; Merritt, Victoria; Yetto, Joseph M.; Pasquina, Paul F.; Tsao, Jack W.
Abstract Background Mirror therapy has been demonstrated to reduce phantom limb pain (PLP) experienced by unilateral limb amputees. Research suggests that the visual feedback of observing a limb moving in the mirror is critical for therapeutic efficacy. Objective Since mirror therapy is not an option for bilateral lower limb amputees, the purpose of this study was to determine if direct observation of another person's limbs could be used to relieve PLP. Methods We randomly assigned 20 bilateral lower limb amputees with PLP to visual observation (n = 11) or mental visualization (n = 9) treatment. Treatment consisted of seven discrete movements which were mimicked by the amputee's phantom limbs moving while visually observing the experimenter's limbs moving, or closing the eyes while visualizing and attempting the movements with their phantom limbs, respectively. Participants performed movements for 20 min daily for 1 month. Response to therapy was measured using a 100‐mm visual analog scale (VAS) and the McGill Short‐Form Pain Questionnaire (SF‐MPQ). Results Direct visual observation significantly reduced PLP in both legs (P < 0.05). Amputees assigned to the mental visualization condition did not show a significant reduction in PLP. Interpretation Direct visual observation therapy is an inexpensive and effective treatment for PLP that is accessible to bilateral lower limb amputees.